The future is here! Recognizing the need to revitalize and transform business education via digital integration - Philip, Jestine; Schmidt, Gordon B.; Simha, Aditya; Rosen, David (Business Horizons, 2026)
Business education is undergoing rapid transformations thanks to advancements in emerging technologies. Business school leaders are engaging in identifying approaches to revitalize business education, preparing students to succeed in a technologically advancing workplace. Primarily anchored in the concept of digital transformation, our article provides practical guidance to help business schools integrate artificial intelligence (AI) into their curricula and infrastructure, benefiting students, faculty, administration, and leadership. We offer a roadmap that lays out current industry trends and articulates pertinent action items, related cost efforts, and associated benefits for business education. This article positions business schools to instill a human-AI augmentation mindset in students, faculty, staff, and leadership that prepares them to work with ever-changing technologies. Regularly revising business course curricula to stay aligned with evolving industry needs is key to providing topical content and meaningful skill development opportunities for students. We argue that these efforts directly enhance student employability and learning, better preparing students to succeed in the increasingly technology-enabled workplace. © 2026 Kelley School of Business, Indiana University. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Artificial intelligence (AI); Business schools; Digital transformation; Generative AI (GenAI); Human-AI augmentation mindset; dept.mgt

How Do Firms Build Green Supply Chain Learning System? A Theoretical Framework and Directions - Birasnav, M.; Han, Seungmin; Arora, Ridhi; Sangar, Ruby (Corporate Social Responsibility and Environmental Management, 2026)
Keywords: Green innovation; Mechanism (biology); Perspective (graphical); Resource (disambiguation); Supply chain; Supply chain management; Workforce; corporate social responsibility; dept.mgt; environmental performance; exploitation; exploration; green supply chain; leadership; learning system

Framing the future: how museums shape sustainability mindsets in business education - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (The Power of Arts-Based Pedagogies: Transforming Mindsets to Shape Our Future, 2026)
Recent research proposes that arts-integrated teaching approaches in business education can nurture students' aesthetic sensitivity and emotional capacities, such as self-awareness and empathy. In this chapter, we examine the pedagogical possibility of art appreciation in art museums as a consciousness-raising practice, especially for the sake of cultivating business students' environmental awareness in two different contexts. We have analyzed American and Russian students' reflective essays based on their museum visits in order to explore how business students make sense of their aesthetic experiences and how art appreciation helps them to develop their sustainability mindset in a creative learning space. Through attentive viewing of the works of art, students have learned some key insights from their aesthetic appreciation at art museums. These insights not only facilitated honing their emotional skills, but also deepened their environmental awareness and heightened their sense of personal empowerment to act upon these newly acquired insights and values ensuing from art appreciation. After identifying six key themes extracted from both groups of students' essays based on their museum learning, we further discuss the pedagogical implications of contemplative art appreciation in museums as a means of contributing to more innovative and sustainable management education. © 2026 selection and editorial matter, Ekaterina Ivanova, Isabel Rimanoczy and Divya Singhal; individual chapters, the contributors.
Keywords: dept.mgt

Quality management and safety performance: the influence of ethical leaders among public sector employees - Birasnav, M.; Dahiya, Rinki; Dalpati, Avadhesh (The TQM Journal, 2026)
Keywords: Ethical leadership; Incentive; Job satisfaction; Motivation for QM implementation; Perceived safety performance; Public sector; Quality (philosophy); Structural equation modeling; Survey data collection; Test (biology); Work (physics); dept.mgt